2012
DOI: 10.1128/jb.00871-12
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequences for Six Rhodanobacter Strains, Isolated from Soils and the Terrestrial Subsurface, with Variable Denitrification Capabilities

Abstract: We report the first genome sequences for six strains of Rhodanobacter species isolated from a variety of soil and subsurface environments. Three of these strains are capable of complete denitrification and three others are not. However, all six strains contain most of the genes required for the respiration of nitrate to gaseous nitrogen. The nondenitrifying members of the genus lack only the gene for nitrate reduction, the first step in the full denitrification pathway. The data suggest that the environmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 17 publications
3
36
0
Order By: Relevance
“…In contrast, when nitrite was used as the first electron acceptor, nirS sequences similar to those found in Gammaproteobacteria, in particular Rhodanobacter sp., were the most abundant. A recent analysis of complete genome sequences of six Rhodanobacter strains isolated from soils have revealed that at least three of them lack the ability to reduce nitrate [50]. Similarly to what has been observed with the nirS gene, bacteria enriched when nitrite was used suggest the exclusive use of nitrite as electron acceptor.…”
Section: Discussionmentioning
confidence: 80%
“…In contrast, when nitrite was used as the first electron acceptor, nirS sequences similar to those found in Gammaproteobacteria, in particular Rhodanobacter sp., were the most abundant. A recent analysis of complete genome sequences of six Rhodanobacter strains isolated from soils have revealed that at least three of them lack the ability to reduce nitrate [50]. Similarly to what has been observed with the nirS gene, bacteria enriched when nitrite was used suggest the exclusive use of nitrite as electron acceptor.…”
Section: Discussionmentioning
confidence: 80%
“…Even though our protocol was validated to detect nitrifiers (Fig. S4), we also found no nitrifiers in the commercial inoculum, which was dominated by Rhodanobacter, a known denitrifying genus [11].…”
Section: Narrativementioning
confidence: 81%
“…Some nitrate-reducing organisms carry out only the first step, the dissimilatory reduction of nitrate to nitrite, while others reduce nitrate to ammonium by a process called nitrate ammonification (11). On the other hand, some microorganisms cannot reduce nitrate but contain later steps of the denitrification pathway (12).…”
mentioning
confidence: 99%